2008
DOI: 10.1088/0741-3335/51/1/012001
|View full text |Cite
|
Sign up to set email alerts
|

Collisionless damping of short wavelength geodesic acoustic modes

Abstract: Collisionless damping of geodesic acoustic mode (GAM) excited in the large safety factor (q) region of a tokamak plasma is investigated taking into account the effects of finite ion Larmor radius and guiding-center drift orbit width as well as parallel electric field contributions. A corresponding analytical expression for the damping rate including higher-order harmonics of ion transit resonances is systematically derived and agrees well with numerical results in its validity regime.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

8
135
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 89 publications
(143 citation statements)
references
References 13 publications
8
135
0
Order By: Relevance
“…The GAM is usually driven nonlinearly by plasma microturbulence. There is much linear study on GAM's damping due to collision and ion Landau resonance [8][9][10][11][12][13][14][15][16] and on GAM's radial propagation due to finite thermal ion gyroradius and plasma temperature profile inhomogeneity [13,14]. Nonlinear studies found that that GAM can be driven by plasma microturbulence [13,[17][18][19], consistent with experimental observation of GAM in the plasma edge region [20][21][22].…”
Section: Introductionsupporting
confidence: 53%
“…The GAM is usually driven nonlinearly by plasma microturbulence. There is much linear study on GAM's damping due to collision and ion Landau resonance [8][9][10][11][12][13][14][15][16] and on GAM's radial propagation due to finite thermal ion gyroradius and plasma temperature profile inhomogeneity [13,14]. Nonlinear studies found that that GAM can be driven by plasma microturbulence [13,[17][18][19], consistent with experimental observation of GAM in the plasma edge region [20][21][22].…”
Section: Introductionsupporting
confidence: 53%
“…The procedure is almost the same as described in Ref. 23, but can still be simply outlined here with the expressions in Eqs. ͑6͒-͑8͒ for the sake of clarity and completeness.…”
Section: B the Solution In The Large Orbit Drift Width Limitmentioning
confidence: 99%
“…For nonresonant ions, the large orbit drift width limit can be relaxed more in the expansion. 23 We only need t / ϳ 1 / q Ӷ 1 and also d / ϳ k ti Ӷ 1. Without losing the generality, we can put these two terms into the same order.…”
Section: B the Solution In The Large Orbit Drift Width Limitmentioning
confidence: 99%
See 1 more Smart Citation
“…There is no fluctuations on the curves. As a comparison, we then let k = 0.1375 as done in the TEM-PEST simulation [6], COGENT simulation [7] and theoretical calculation [10,16]. It is found that in this condition, the damping rate increases with M first.…”
mentioning
confidence: 99%